Negotiating trust and struggling for control: everyday narratives of unwanted disclosure of HIV status among people with HIV in Australia. Issue 1 (2nd January 2018) - Bell, Stephen; Aggleton, Peter; Slavin, Sean
ABSTRACT: Despite the frequent occurrence of unwanted disclosure of HIV status in Australia, there is little understanding of its determinants and consequences. This paper offers an analysis of lived experiences of unwanted disclosure amongst 28 people with HIV in urban settings in Australia. Of the 28 individuals interviewed, 17 men and 8 women had experienced unwanted disclosure of their HIV status by other people in work, health, social and other settings. Through the lenses provided by the concepts of habitus and agentic practice, this paper focuses on unintentional and deliberate practices of unwanted disclosure, and the consequences that may arise from this. Findings reveal how unwanted disclosure may lead to reflexive and agentic action among people with HIV as they struggle to reclaim control over their lives and how they are perceived. Despite what is sometimes assumed, the negative social responses the HIV epidemic has given rise to persist in Australia. Some 30 years into the epidemic, findings highlight the need to establish a social climate that is intolerant of unwanted disclosure, and which recognises the damage it may cause.